2020
DOI: 10.3390/plants9121760
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Pollen Activation and the Role of H+-ATPase in Pollen Germination in Blue Spruce (Picea pungens)

Abstract: Pollen is a highly specialized structure for sexual plant reproduction. Early stages of pollen germination require the transition from dormant state to active metabolism. In particular, an important role during this early phase of angiosperm pollen germination is played by H+-ATPase. Very little is known about pollen activation in gymnosperm species, and information on the involvement of H+-ATPase is lacking. We tracked four indicators characterizing the physiological state of pollen: membrane potential, intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Later, data on the respiration of pine ( Pinus ponderosa) pollen grain suspension were obtained by infrared spectroscopy: in the first 24 h of incubation, CO 2 release was low, after which it increased rather sharply, the most active increase was observed after 48 h of incubation [ 63 ]. For blue spruce ( Picea pungens ), the pollen of which germinates faster than that of pine, oxygen consumption registered with the Clarke electrode increased sharply from 2 to 9 h of incubation and the maximum coincided with the pollen tube appearance; then, during early stages of pollen tube growth, the level of respiration decreased by about 30% [ 64 ]. In the same species, infrared spectroscopy showed that from 8 h of incubation, the release of carbon dioxide increased sharply and almost linearly [ 63 ].…”
Section: Biochemical Regulation Of Conifer Pollen Germination and Pollen Tube Growthmentioning
confidence: 99%
See 4 more Smart Citations
“…Later, data on the respiration of pine ( Pinus ponderosa) pollen grain suspension were obtained by infrared spectroscopy: in the first 24 h of incubation, CO 2 release was low, after which it increased rather sharply, the most active increase was observed after 48 h of incubation [ 63 ]. For blue spruce ( Picea pungens ), the pollen of which germinates faster than that of pine, oxygen consumption registered with the Clarke electrode increased sharply from 2 to 9 h of incubation and the maximum coincided with the pollen tube appearance; then, during early stages of pollen tube growth, the level of respiration decreased by about 30% [ 64 ]. In the same species, infrared spectroscopy showed that from 8 h of incubation, the release of carbon dioxide increased sharply and almost linearly [ 63 ].…”
Section: Biochemical Regulation Of Conifer Pollen Germination and Pollen Tube Growthmentioning
confidence: 99%
“…These data are difficult to compare, since in the last study, starting at 8 h, respiration was measured once a day, and in the first one, the points of 9 and 14 h were compared. However, 8 and 9 h points, respectively, were marked as tipping points in the studies, which appeared to be associated with the moment of the tube emergence [ 64 ].…”
Section: Biochemical Regulation Of Conifer Pollen Germination and Pollen Tube Growthmentioning
confidence: 99%
See 3 more Smart Citations